Changes in living arrangements and mortality among older people in China - Zhixin Feng; Jane Falkingham; Xiaoting Liu; Athina Vlachantoni (Elsevier, 2017)
Living arrangements in later life are dynamic, with changes associated with life events such as widowhood or moves into an institution. Previous research has found particular changes in living arrangements to be associated with an elevated risk of mortality. However, research in this area within the context of China is limited, despite China being home to the world's largest population of older people. This study investigates the impact of changes in living arrangements on older persons' survival using the Chinese Longitudinal Healthy Longevity Survey from 2002 to 2011. The original sample was 16,064 in 2002, and this study includes 6191 individuals who survived in 2005 and had complete information of track record in later waves. Changes in living arrangements are examined between 2002 and 2005. Cox-proportional hazards models are then used to investigate the association between the dynamics of living arrangements and respondents' survival status from 2005 to 2011 . Results show that men and women who lived in an institution in both 2002 and 2005, or who moved into an institution from living with family faced a greater risk of dying compared to those continuing to live with family. By contrast, continuing to live with family or alone, or moving between living with family and living alone, were not associated with an increased mortality risk, although there were some differences by gender. The institutional care sector in China is still in its infancy, with provision based on ability to pay market fees rather than need associated with age-related function impairment. The findings show that living in, or moving into, an institution is associated with a high mortality risk therefore requires further investigation in the context of a rapidly changing Chinese society.